[RETRACTED] Green Marketing Mix and Eco-Label Consumer Behavior: The Role of Environmental Knowledge - Krismanto Erick Tobush Naibaho; Martin Luter Purba; Frederick Saroha Silaban; Yehezkiel Dosdoy Siagian (Manajemen dan Bisnis, 2026)
"RETRACTED. This article has been retracted by the Editorial Board due to a case of duplicate/multiple submission. See the retraction notice for details. Environmental degradation has been identified as a contributing factor to natural disasters, while public awareness toward environmental sustainability in Indonesia remains relatively low. In response, businesses have begun adopting environmentally oriented marketing strategies, particularly the green marketing mix, which includes green products, green promotion, and green people. As consumers acquire greater environmental knowledge, they develop a better understanding of the value and quality of eco-friendly products, which in turn influences their purchasing behavior. This study aims to examine the factors influencing consumer behavior toward eco-labeled products. A quantitative approach was employed using purposive sampling, involving 200 respondents. Primary data were collected through structured questionnaires distributed based on predetermined criteria. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.3 software. The findings are expected to provide both theoretical contributions and practical insights, particularly for firms producing eco-friendly products in designing effective marketing strategies. Specifically, this study highlights the role of green promotion as an important driver of environmental knowledge, which subsequently shapes consumer behavior toward eco-labeled products.